Value Creating Education Philosophy and the Womanist Discourses of African American Women Educators: Soka Education and Womanist Education Philosophy - Estrada Jones, Paula (Journal of Interdisciplinary Studies in Education, 2020)
The paper documents the initiative of two African American women educators who have utilized these theoretical approaches to solve the educational challenges in their respective communities. Marva Collins and Corla Hawkins decided to build schools in their own communities after realizing that the public schools were not equipped to educate minorities. The story of these two women demonstrates that individuals can address systemic injustices in their communities. Collins and Hawkins were not wealthy. What they possessed was a passion for helping others. Their example can inspire more individuals to take steps using liberating philosophies, like value-creating education and womanist approaches in education, to transform the state of education in their communities.